Guerreiro ramos and the sociology in "shirtsleeves": an interventionist proposition in social change processes - Rezende, Maria José de (Cadernos CERU, 2006)
The main purpose of this article is to map Guerreiro Ramos' discussions on the necessity of implementing a pragmatic sociology in the country. Based on presuppositions that his reflections on the urgency for constituting a purposed knowledge in the country, several debates, propositions and questionings were surfaced, and involved several thinkers from the 50s. They were concerned about the following issue: which course should sociology in Brazil follow in the second half of the 20th century? The reflections upon the man of science's actions and the discussions on the precariousness of the academic as well as of the "canned" sociology caused, in several social scientists, a meaningful rejection to his intervention propositions in the social change processes which were in progress at that moment. It is considered that the courses opened by the debates stimulated by his interventionist propositions, shed some light on the difficulties and dilemmas about the role of the intellectual in the world, today.